Changes in Subjective-Objective Sleep Discrepancy Following Inpatient Cognitive Behavior Therapy for Insomnia. Issue 5 (September 2019) - Crönlein, Tatjana; Lehner, Astrid; Schüssler, Petra; Geisler, Peter; Rupprecht, Rainer; Wetter, Thomas C.
Abstract: Discrepancy between objective and subjective sleep parameters is a frequent symptom in persons suffering from insomnia. Since it has an impairing effect on daytime well-being and neglects possible positive objective improvements, it would be useful if it was treated. Apart from hypnotics, cognitive behavior therapy (CBT-I) is the therapy of choice for chronic forms of insomnia. However, there is limited information about whether CBT-I can also improve subjective-objective sleep discrepancy. We investigated a large sample of patients showing chronic forms of insomnia regarding their subjective-objective sleep discrepancy pre and post CBT-I. Objective sleep data were obtained from 3 nights (2 baseline nights and 1 night after therapy) using polysomnography in our sleep laboratory. All 92 patients participated in a 14-day inpatient program with CBT-I including psychoeducation about subjective-objective sleep discrepancy. Repeated measures analyses showed an improvement in subjective-objective sleep discrepancy parameters after CBT-I. Those parameters were also correlated with perceived quality of sleep. We conclude that CBT-I is a useful tool to improve subjective-objective sleep discrepancy in patients showing chronic forms of insomnia. Highlights: Subjective-objective sleep discrepancy (SOSD) is often found in insomnia patients. Cognitive Behavior Therapy (CBT-I) is standard in the treatment of insomnia. There is limited information about whether CBT-I can change SOSD. We investigated a large sample of patients regarding SOSD pre and post CBT-I. An improvement in SOSD was seen after CBT-I.